Features of the attitude to vaccination against COVID-19 in Russia - S. A. Galkin; D. G. Naidenko; A. N. Kornetov; V. L. Goiko; M. G. Myagkov (Бюллетень сибирской медицины, 2022)
Background. 1.5 years after the registration of the first vaccine against COVID-19 in Russia, national herd immunity reached only 49.7%. It is obvious that the success of vaccination measures depends on the readiness of the population for immunization and their attitude to the vaccine.The aim of the study was to research the attitude to vaccination against a new coronavirus infection among various socio-demographic population groups in Russia.Materials and methods. The study was conducted online by distributing via social networks a direct link to an electronic form with questions about the attitude to the COVID-19 pandemic and vaccination. A total of 2,786 people (of whom 66.9% were women) aged 16 to 77 years took part in the online survey.Results. It was shown that distrust of vaccination was more often expressed by women and younger people.  A targeted approach to these population groups can improve the results of awareness-raising and preventive measures in the context of an ongoing pandemic.